Simvastatin dengan Senyawa Turunan Β-Siklodextrin - Cristy, Devina Wahyu Astaning; Harmastuti, Nuraini; Mardiyono, Mardiyono (Journal of Telenursing (JOTING), 2024)
This study aims to determine the profile of the inclusion complex formed between simvastatin and β-cyclodextrin and its derivatives. To determine the level of stability and determine the solubility level of the inclusion complex formed between simvastatin and β-cyclodextrin and its derivatives (2-hydroxypropyl-β-cyclodextrin and 2,6-di-O-methyl-β-cyclodextrin) in water solvent.The method used is qualitative descriptive using the molecular docking method, modeling and anchoring the inclusion complex model.The research results show that the simvastatin/HP-β-CD inclusion complex has a higher level of solubility in water solvents compared to the simvastatin/β-CD and simvastatin/DM-β-CD inclusion complexes, with a ΔGsolvation value of -1032.34 kJ/mol.Conclusion: Simvastatin is able to bind to the cavity of 2-hydroxypropyl-β-cyclodextrin, 2,6-di-O-methyl-β-cyclodextrin, and simvastatin/β-cyclodextrin with the following order of bond strength: simvastatin/2-hydroxypropyl-β -cyclodextrin > simvastatin/2,6-di-O-methyl-β-cyclodextrin > simvastatin/β-cyclodextrin. Keywords: Inclusion Complex, Molecular Docking, Molecular Dynamics Simulation, Β-Cyclodextrin, Simvastatin.